PENYELESAIAN SENGKETA MELALUI PERADILAN TATA USAHA NEGARA TERHADAP PEMBATALAN KONTRAK LUMPSUM SEPIHAK - Abu Thalhah Al Anshari; Maheswari Queena Dewani; Shintia Januarita; Wilhelmina Setia Atmadja (LPPM STIH Awang Long, 2025)
Another form of potential dispute that wil arise is in the form of a contractual relationship that occurs due to a lump sum contract using a type of construction contract from the government to the private sector. This form can be seen from the inequality of the parties' positions. In practice,